Gestão do conhecimento com foco na segurança do paciente: proposta de um modelo de gestão para hospitais - Silva, Carla Roberta Moreira da (2015)
Incidents regarding the safety of the patient happen for many reasons and are increased by the inefficiency of the mechanism to register notifications. They enlighten the knowledge, the dimension and the intensity of the problem that afflict hospitals when it comes to mistakes made during the assistance. The prevention of incidents is based on legal and ethic norms and is a challenge for the World Health Organization and the responsible organs. By increasing the notifications, those in charge for the nucleus of patient safety have more information and can set strategies to avoid adverse events. The objective of this work is to present a proposal of a knowledge management model developed to increase the volume of the registrations of notifications regarding incidents of patient safety in public hospitals. To subsidize the proposal of the model, this study was exploratory and the methodology of literature review was applied. In order to complete this research, notifications of patient safety developed by a multi-professional team in 2014 at a public clinic were retrospectively analyzed. This dissertation also presented a descriptive quantitative approach, which occurred through the application of a structured questionnaire on the members of the multi-professional team of the clinic. Data found on the documental research were confronted with the questionnaire results and everything seems to show that if professionals adopted the culture of notifying, as they theoretically showed, the volume of registrations in a one year period would have been more expressive. After analyzing the collected data, a proposal of a knowledge management model was elaborated, which can collaborate with the development of more effective preventive strategies. That is, everyone can benefit from it; the patient will have a safer attendance; the professional will work more systematically; society will reduce extraordinary costs with procedures performed because of unnecessary damages. It is important that the involved people receive constant feedbacks about the benefits of their efforts when it comes to adopting the practice of notifying.